Content analysis of emergency enforcement of community activity restrictions News Portals on Tirto and Media Indonesia Online News Portals for the Period 3 – 20 July 2021 - Nafza, Gisellya Noorrahma Shalihatan; Junaedi, Fajar (COMMICAST, 2023)
The purpose of this study was to determine the frequency and trend of emergency PPKM or Pemberlakuan Pembatasan Kegiatan Masyarakat (Enforcement of Community Activity Restrictions) news on online news portals Tirto and Media Indonesia in the period 3 – 20 July 2021. These included news formats, news elements, news values, news sections, news materials. and interviewing resource persons. The approach uses descriptive quantitative with content analysis method. The research population is all the contents of the emergency PPKM news in Tirto and Media Indonesia, totaling 170 news stories. The results showed Tirto and Media Indonesia chose news in the form of hard news. All news is presented with complete elements. The difference is as follows. Media Indonesia, in their reporting, gives more of the portion of informants to bureaucrats. On the other hand, Tirto only took fewer informants from the bureaucrats.